Job Descriptions and Communication Effect on Teachers’ Job Satisfaction in Vocational High School - Sherly; Kisno (Jurnal Pendidikan dan Pengajaran, 2024)
Job satisfaction is one of the factors that influence the achievement of successful educational goals. This factor is an exciting and vital research object in human resource management, especially in vocational education. This study attempts to reveal job description and communication's simultaneous and partial influence on teacher job satisfaction. This study is critical because understanding the factors that influence job satisfaction can help formulate more effective and strategic management policies, ultimately improving the overall quality of education. A total of 33 teachers were involved as the population and sample in this study, and data were collected through a survey. A questionnaire was developed as a research instrument, and the hypothesis was tested using the t-test and F-test. Multiple linear regression was applied to analyze the collected data. This study found that job description and communication simultaneously influenced teacher job satisfaction. In other words, based on the coefficient of determination, job description and communication simultaneously influenced job satisfaction by 58.4%, partially the largest 52% by job description and 38.2% by communication variables. Follow-up to this research is suggested to explore other factors that may influence teacher job satisfaction and develop interventions that can improve job descriptions and communication in the context of vocational education.